Fact and Opinion - Hutchins, Debby; Kelley, David (Informal Logic)

(untitled) (Informal Logic, 2023)
Our goal is to analyze the distinction between factual statements and opinions from a philosophical—specifically an epistemological—perspective. Section 1 reviews the most common criteria for drawing the distinction, which while inadequate, as explained in Section 2, still plays an important cultural and political role. In Section 3, we argue that the difference between factual statements and opinions does not involve a single criterion. Instead, the conceptual structure of the terms ‘fact’ and ‘opinion’ is analogous to that of natural kinds—terms with multiple dimensions. We expect that improved theory will lead to improvements in pedagogy, decision-making, and public discourse. But these consequences are not our chief focus.